The Open Society as an Enemy - J. McKenzie, Alexander (LSE Press, 2024)
Nearly 80 years ago, Karl Popper gave a spirited philosophical defence of the Open Society in his two-volume work, The Open Society and Its Enemies. In this book, J. McKenzie Alexander argues that a new defence is urgently needed because, in the decades since the end of the Cold War, many of the values of the Open Society have come under threat once again. Populist agendas on both the left and right threaten to undermine fundamental principles that underpin liberal democracies, so that what were previously seen as virtues of the Open Society are now, by many people, seen as vices, dangers, or threats. The Open Society as an Enemy interrogates four interconnected aspects of the Open Society: cosmopolitanism, transparency, the free exchange of ideas, and communitarianism. Each of these is analysed in depth, drawing out the implications for contemporary social questions such as the free movement of people, the erosion of privacy, no-platforming and the increased political and social polarisation that is fuelled by social media. In re-examining the consequences for all of us of these attacks on free societies, Alexander calls for resistance to the forces of reaction. But he also calls for the concept of the Open Society to be rehabilitated and advanced. In doing this, he argues, there is an opportunity to re-think the kind of society we want to create, and to ensure it is achievable and sustainable. This forensic defence of the core principles of the Open Society is an essential read for anyone wishing to understand some of the powerful social currents that have engulfed public debates in recent years, and what to do about them. Early praise for The Open Society as an Enemy ""Many people have waded into the culture wars, but very few have rigorously and engagingly examined why the way we think about each other is changing. J McKenzie Alexander probes the assumptions we make about contemporary society and exposes who benefits from outrage and polarisation. Everyone who talks about the 'open society' and what it means should read this book."" — Ros Taylor, author of The Future of Trust “I’m not sure I’ve ever read a work of political philosophy as forensic and yet so full of heart and humour as Jason McKenzie Alexander’s The Open Society as an Enemy. It’s not simply that the book applies an astonishing breadth of expertise to the most neuralgic issues of our time - from political and economic polarisation, political extremism, climate change and the lottery of birthplace, to no-platforming and the discursive anarchy of social media - it’s that McKenzie Alexander writes with deep empathy for those who doubt, by now, that the open society, in its various forms, can still work, and this makes his defence of it all the more compelling and complete.” — Abby Innes, author of Late Soviet Britain: Why Materialist Utopias Fail